Atmospheric reaeration in the Chao Phya River estuary - Sermpol Ratasuk; Pescod, M.B.; Ackermann, Norbert L.; Arbhabhirama Anat (Bangkok : Asian Institute of Technology, 1968)
Three different methods were used in an attempt to determine the atmospheric reaeration coefficient of the Chao Phya River estuary. One method of calculation using mean tidal velocities and hydraulic depths was found to be inapplicable to the estuary. In the second method, data obtained in a March 1967 pollution survey were used to calculate the reaeration coefficient by making an oxygen balance. This method, in spite of its many disadvantages, gave more reliable results than those given by the other methods, The third method of in-situ direct measurement using a small polythene sphere gave values of the coefficient lower than those obtained using the oxygen balance method. In the oxygen balance method, BOD and dissolved oxygen data were adjusted to half-tide conditions using chlorinity data. A BOD distribution curve and an oxygen sag curve for each rate of river discharge were plotted and mean local BOD and dissolved oxygen concentrations were determined. Local longitudinal dispersion coefficients were calculated using chlorinity data in the reach of high chlorinity and from hydraulic elements in the reach of low chlorinity. These data were used in solving the oxygen balance equation, developed specifically for the Chao Phya River estuary, using an IBM 1130 computer to obtain local values of the reaeration coefficient. The average value of the reaeration coefficient for the Chao Phya River estuary in the dry season, obtained from the oxygen balance method, was 0.205 per day (base 10) and this value is recommended for future use in pollution control work on the estuary.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1968
Keywords: Water -- Aeration